Tenaga Kesehatan Selama Pandemi: Pentingnya Peran Psychological Well Being sebagai Mediasi Quality of Work Life dan Stres Kerja terhadap Perceived Productivity dalam Masa Pandemi Covid-19 di Rumah Sakit Swasta Jakarta - Yohanes Ariyanto Seno; Rina Anindita; Idrus Jus’at (Syntax Corporation Indonesia, 2022)
Entering the beginning of 2020 external conditions globally in some parts of the world experienced a covid-19 pandemic and especially in Indonesia this case began to increase in February 2020. To respond to the state of the covid-19 virus pandemic in Indonesia which continues to increase massively, it requires health workers as the vanguard. Hospitals in providing services related to covid-19 need to pay attention to aspects that can support the productivity of health workers in order to increase perceived productivity. Many factors that affect perceived productivity, including quality of work life, work stress, psychogical well being, and so on. This study aims to analyze the effect of quality of work life and work stress on perceived productivity in health workers at Jakarta Private Hospital with psychological well being as a mediation variable in the covid-19 pandemic.The research design used is quantitative analysis research with a causality approach. The data source is obtained in the form of primary data. The authors used a survey method with questionnaire instruments distributed to 152 sample people. Analysis of questionnaire data is conducted using SEM and illustrated through descriptive statistics. The results showed that quality of work life and work stress had a positive influence on perceived productivity with psychological well being as mediation in health workers working in the covid-19 pandemic in jakarta private hospitals. Thus, Jakarta's private hospitals can focus more on these research variables in order to improve in thefuture.